Assessment of magnesium status in newly diagnosed diabetic children: measurement of erythrocyte magnesium level and magnesium tolerance testing - Simşek, Enver; Karabay, Meltem; Kocabay, Kenan (The Turkish Journal of Pediatrics, 2005)
The aim of this study was to investigate the relationship between serum, erythrocyte and urine magnesium levels and retained magnesium percentage in newly diagnosed diabetic children. In a cross-sectional study, 34 children with insulin dependent diabetes mellitus (IDDM) and 21 healthy age- and sex-matched control subjects were screened for their serum, erythrocyte, and urine magnesium levels. Magnesium tolerance test was performed on diabetic and control subjects. Serum and erythrocyte magnesium levels in diabetic children were significantly lower than in healthy controls (plasma magnesium, p